Fatherless Child Pada Wakana Gojo Dalam Anime Sono Bisque Wa Koi Wo Suru Karya Keisuke Shinohara - Hendra, Ivonne (KIRYOKU, 2024)
The study was titled Fatherless Child In Wakana Gojo in Keisuke Shinohara's Sono Bisque Doll Wa Koi Wo Suru anime. This study analyzed the depiction of a fatherless child and the efforts of the character Wakana Gojo to overcome his fatherless child. Wakana Gojo is the main character in the anime sono bisque doll wa koi wo suru which shows maladaptive behavior such as difficulty in social relationships with people around him, despair, emptiness, and fear of rejection. This study used unstructured observation methods, descriptive observation. The theories used in analysis are the psychological theory of literature and the theory of semiotics. The analysis results in this study show Wakana Gojo's fatherless behavior, namely: 1) Fear of rejection; 2) Loss of trust in others and withdrawing from the social environment. Wakana Gojo's fatherless attitude was due to his father's abandonment at a young age. Although Wakana Gojo has received love from the grandfather who raised him, it is still not enough, because of an empty hole in his heart.